Phoneme in Minangkabau Language Between Padang Dialect and Lintau Buo Dialect - Yessy Marzona (Jurnal Ilmiah Langue and Parole, 2019)
Minangkabau people have many dialects, every region has one dialect. Padang and Lintau do not have same dialect. Padang city uses Minangkabau Language because this is a standard language eventhought they has many varieties dialect use in daily communication.Padang and Lintau Buo, both of which are often called Minangkabau language, are different dialect rather than different dialect of one language because they are not mutually intelligible in their spoken form. The problems are the difference between phoneme in Padang and Lintau Buo dialect and phonem deletion and additional in Padang and Lintau Buo dialect. There are differences between phoneme of Padang dialect and Lintau Buo dialect. The difference of phoneme can be seen in their vowels and consonants in several position of phoneme such as initial, medial and final.Phoneme